The impact of the COVID-19 pandemic on cancer care - Richards, Mike; Anderson, Michael; Carter, Paul; Ebert, Benjamin L.; Mossialos, Elias (Nature cancer, 2020)
The COVID-19 pandemic has disrupted the spectrum of cancer care, including delaying diagnoses and treatment and halting clinical trials. In response, healthcare systems are rapidly reorganizing cancer services to ensure that patients continue to receive essential care while minimizing exposure to SARS-CoV-2 infection.